GE_GERICHTE A/1027/2023 vom 27. August 2024 - GE Cour de justice (2024)
DROIT D'ÊTRE ENTENDU;PERSONNE AUTORISÉE À SIGNER;SIGNATURE | Cst.29.al2; RCI.11.al4; LAT.19.al1; LAT.22.al2.letb; LCI.14.al1; LForêts.11.al4; RCI.3.al3; LCI.15; LAC.30.al1.letm